2021
DOI: 10.1590/1678-7757-2021-0180
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of injectable platelet-rich fibrin in the erosive oral lichen planus: a split-mouth, randomized, controlled clinical trial

Abstract: Efficacy of injectable platelet-rich fibrin in the erosive oral lichen planus: a split-mouth, randomized, controlled clinical trial* Objective: Our study compared the effects of injectable platelet-rich fibrin (i-PRF) with those of corticosteroids in the treatment of erosive oral lichen planus (EOLP). Methodology: This split-mouth study included 24 individuals diagnosed histopathologically with bilateral EOLP. One bilateral lesion was injected with i-PRF, whereas the other was injected with methylprednisolone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
(9 reference statements)
1
16
0
Order By: Relevance
“…It has been shown that i-PRF can be as effective as corticosteroid injection, which is considered the gold standard in the treatment of EOLP lesions. 83 There is no clinical study involving i-PRF application in oral lesions of autoimmune bullous diseases.…”
Section: Current Practices and New Methods In Autoimmune Bullous Dise...mentioning
confidence: 99%
“…It has been shown that i-PRF can be as effective as corticosteroid injection, which is considered the gold standard in the treatment of EOLP lesions. 83 There is no clinical study involving i-PRF application in oral lesions of autoimmune bullous diseases.…”
Section: Current Practices and New Methods In Autoimmune Bullous Dise...mentioning
confidence: 99%
“…Besides, recent research demonstrated that i-PRF has a positive and curative effect on erosive lichen planus (30). In another study, Johns et al (36) documented that pulp revascularization shows disinfection with photodynamic therapy combined with platelet-rich fibrin leads to satisfactory root development in necrotic immature teeth.…”
Section: Areas Of Use Of Platelet-rich Fibrin In Dentistrymentioning
confidence: 99%
“…26 Two further studies demonstrated that i-PRF injections significantly improved symptomatic oral lichen planus. 27,28 In a final clinical study, Negah and colleagues investigated i-PRF administration for the management of root resorption in 10 healthy patients. 29 It was reported that the clinical evaluation resulted in the resolution of signs and symptoms through a 12-month follow-up period in all cases.…”
Section: Us E Of I-prf For Improved Wound He Aling In the Or Al C Avit Ymentioning
confidence: 99%
“…In a clinical study by Kiziltoprak and colleagues, higher palatal wound epithelialization and lower bleeding and pain scores were found in the i‐PRF group than in the control group 26 . Two further studies demonstrated that i‐PRF injections significantly improved symptomatic oral lichen planus 27,28 . In a final clinical study, Negah and colleagues investigated i‐PRF administration for the management of root resorption in 10 healthy patients 29 .…”
Section: Use Of I‐prf For Improved Wound Healing In the Oral Cavitymentioning
confidence: 99%